Cytoarchitectural Pattern of Hepatocellular Carcinoma (HCC) in Ahmadu Bello University Teaching Hospital Zaria, Nigeria - Okpoghono, J.*, Achuba, F.I. and George, B.O. (Sokoto Journal of Medical Laboratory Science)
This study examined the influence of M. myristica extracts on lipid profile of rats fed crude petroleum oil contaminated catfish diet. Thirty albino wistar rats were divided into six groups of five rats each. Group 1:  control, group 2: rats were fed crude petroleum oil contaminated catfish diet (CPO-CCD) only, group 3: CPO-CCD plus tween 80, group 4: CPO-CCD plus M. myristica water extract (MWE), group 5:  CPO-CCD plus M. myristica ethanol extract (MEE) and group 6: CPO-CCD plus M. myristica diethyl ether extract of (MDEE). Treatment lasted for four weeks. Lipid profile was evaluated were evaluated in serum and tissue homogenate and the results showed significant (p<0.05) increase in total cholesterol (T-Chl), low density lipoprotein cholesterol (LDL-C), triacylglycerol (TAG) and decrease high density lipoprotein cholesterol (HDL-C) levels in the serum and tissues (liver, kidney and brain) of rats fed CPO-CCD only and CPO-CCD plus tween 80 when compared with controls. Treatments of rats with MWE, MEE and MDEE resulted in a significant (p<0.05) decrease in T-Chl, LDL-C, TAG and increase HDL-C levels in the serum and tissues when compare with CPO-CCD only and CPO-CCD plus tween 80. No significant difference (p˃0.05) was observed in the atherogenic index of all the experimental groups.  It is therefore concluded that M. myristica extracts can be utilized in prevention of alterations in lipids in crude petroleum oil toxicity.